Propagation in a Decoupled Twin-Core Waveguide: A Frequency-Domain Analysis - Carlo G. Someda; Federico Cauduro (IEEE Photonics Journal, 2012)
The behavior of two waveguides, which are decoupled at a single frequency when a broadband pulse is launched into one of them, was studied recently in the time domain. We reinvestigate it in the frequency domain. This contributes to the clarification of the scope of the validity of previous results and allows extending them to dispersive waveguides. New results include a power spectral density conservation law and a revised calculation of the pulse breakup distance.